Urgensi Analisis Kelayakan Sebagai Mitigasi Risiko dalam Menjaga Tingkat Kesehatan Penyelenggara LPMUBTI: The Urgency of Feasibility Analysis as Risk Mitigation in Maintaining the Health Level of LPMUBTI Organizers - Meidiana Indah Lestari; Reka Dewantara; Ranitya Ganindha (Faculty of Law, Universitas Brawijaya, 2022)
Fintech Peer to Peer Lending or Information Technology Based Money Lending and Borrowing Service (LPMUBTI) which brings together loan recipients (borrowers) with lenders (lenders) directly through a provider platform, apart from providing convenience for the public, can also provide risks, especially the risk of default, so it is needed mitigating risks in the event of payment default. In the Financial Services Authority Regulation Number 77/POJK.01/2016, it regulates risk mitigation obligations that must be carried out by administrators, but there are no specific risk mitigation aspects. There are no risk mitigation arrangements in the form of loan recipient eligibility analysis. Until now, standards regarding analysis have not been set. eligibility of loan recipients in LPMUBTI. Referring to the problem formulation and objectives of this research, the author uses three types of approaches, including, namely, the statutory approach, the analytical approach, and the conceptual approach. The legal materials used in this research are primary legal materials and secondary legal materials obtained by researchers and then analyzed using descriptive techniques and evaluation techniques. From the results of the review according to the problem definition and techniques described above, LPMUBTI organizers can minimize payment defaults that occur in order to provide protection for lenders who have funds and maintain the health level of LPMUBTI organizers. The conceptualization of the loan recipient eligibility analysis arrangements refers to POJK Number 42/POJK.03/2017 which regulates debtor eligibility analysis in banks, in this case the bank and LPMUBTI have the same risk of default, money lending and borrowing system, the object of money as an agreement and function. intermediation.